(untitled) (New York, 1972)
This book introduce about the civilizing effects of transportation, since it has been our purpose to describe the means by which men have had largely to ignore military developments, except where they have directly contributed to general improvements.
Keywords: Vận tải,Transportation; Lịch sử,History